Analisis dan Penerapan Algoritma C4.5 Untuk Memprediksi Kualitas Penelitian dan Publikasi Ilmiah - Nur Fauza Muhidin; Dudih Gustian; Sihabudin Sihabudin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Research is an obligation for every lecturer in Indonesia. In the midst of increasing publications in Indonesia, however, there is a problem, namely the quality of Indonesian publications which is still low when compared to those countries in Southeast Asia. In this case the C4.5 algorithm is a method that can help predict problems that have been carried out by research on the quality of research and scientific publications. This research was conducted in order to assist the study program to assess the quality of research and scientific publications. From this research, it can be said that by using the C4.5 algorithm, the quality of research and scientific publications can be predicted with a fairly high accuracy, the results of measuring the accuracy of the data obtained from data training with Confusion Matrix with dataTraining testing 81.65%.